2007
DOI: 10.1002/nau.20434
|View full text |Cite
|
Sign up to set email alerts
|

Urethral diverticula: A review and an update

Eric S. Rovner

Abstract: Likely originating from the periurethral glands, female urethral diverticula (UD) are an uncommon but fascinating clinical entity. UD are variable in their presentation and the diagnosis is sometimes difficult and delayed. Modern imaging modalities such as surface coil and endoluminal magnetic resonance imaging (MRI) have added to the diagnostic armamentarium but have also furthered our understanding of UD. Accurate preoperative characterization of the often complex anatomical patterns seen on these imaging st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 45 publications
0
37
0
1
Order By: Relevance
“…A urethral diverticulum is defined as an outpouching of urethral mucosa from the urethra into the urethreo-vaginal potential space (2). It can occur at any point along the course of urethra in both male and females.…”
Section: Discussionmentioning
confidence: 99%
“…A urethral diverticulum is defined as an outpouching of urethral mucosa from the urethra into the urethreo-vaginal potential space (2). It can occur at any point along the course of urethra in both male and females.…”
Section: Discussionmentioning
confidence: 99%
“…20 An association between SUI and UD in females has been shown, 1 although there is no proven cause effect relationship mainly because there are only transversal studies in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…They are found in up to 10% of women with lower urinary tract symptoms. 1 However, it becomes a rare pathology in males, except in the group of patients who suffer from spinal cord injury (SCI), where it could be found in up to 4%. 2,3 According to this prevalence, UD is a common complication in this group of patients, just at the same rate as urinary lithiasis (3.5%).…”
Section: Introductionmentioning
confidence: 99%
“…In a review of the literature by Rovner [4], the author reported a prevalence of up to 10% in women with urinary symptoms. In men, however, it is an exceptional pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of UD is radiologic, based mainly on voiding cystourethrography (VCUG) which is a familiar technique to radiologists [4]. However, the level of diagnostic reliability is also unknown.…”
Section: Introductionmentioning
confidence: 99%